A novel circularly polarized patch antenna based on polarization conversion metasurface for radiation and scattering performance improvement. Issue 12 (18th October 2022) - Liu, Wenxuan; Hong, Run; Qu, Yan; PourMohammadi, Peyman; Yang, Xuexia; Zheng, Qi
Abstract: A new design based on sequential‐rotation arranged polarization conversion metasurfaces (PCMs) is proposed for reducing backscattering and improving radiation performance of circularly polarized (CP) patch antennas. The proposed antenna is composed of a conventional corner‐truncated patch antenna loaded with a PCMs. The configuration of the PCMs increases the operating bandwidth and realized gain, as well as reduce radar cross section (RCS). The relative CP bandwidth (both |S11| < −10 dB and AR <3 dB) is improved to 13.65% due to achieving an additional mode by the PCMs. Also, the peak gain is enhanced by 6.6 dB. Moreover, an in‐band and out‐of‐band RCS reduction is achieved compared with the conventional CP patch antenna due to the polarization conversion characteristic of the PCMs. The maximum RCS reduction is 27.5 dB within the band. This design enables an effective strategy for wideband, high‐gain, and low‐RCS CP patch antennas. A sample operating at C‐band was fabricated and measured, demonstrating a satisfactory match between simulation and measurement results, so verifying the proposed idea.